2022
DOI: 10.3389/fenvs.2022.963264
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between e-commerce growth and solid-waste emissions in china: Open the pathway of green development of e-commerce

Abstract: The growth of the e-commerce industry brings considerable waste. The Chinese government has begun to pay attention to the development of green e-commerce. We first analyze the nexus between China’s e-commerce industry and solid waste and hope to provide some insights into the development of green e-commerce. Considering the cross-sectional dependence of panel data, we adopt the second-generation panel unit root and cointegration tests. Furthermore, the empirical results from the DOLS show that the EKC quadrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
2
2
0
Order By: Relevance
“…However, the magnitude impact of FDI is lower than economic growth and industrialization. The results align with Caiyi et al [52], who found that FDI inflow is harmful and increases solid-waste emissions. On the other hand, the impact of the urban population is favorable, as a 1% increase in the urban population will decrease waste by −2.426% to −2.345% in OECD economies.…”
Section: Long-run Effects By Dksupporting
confidence: 91%
“…However, the magnitude impact of FDI is lower than economic growth and industrialization. The results align with Caiyi et al [52], who found that FDI inflow is harmful and increases solid-waste emissions. On the other hand, the impact of the urban population is favorable, as a 1% increase in the urban population will decrease waste by −2.426% to −2.345% in OECD economies.…”
Section: Long-run Effects By Dksupporting
confidence: 91%
“…In the short term, a rise of 1% in capital, labor force, municipal solid waste recycling, and energy efficiency translates into upticks in economic growth of 0.311%, 0.290%, 0.002%, and 0.130% in order. The signs of the coefficients of independent variables, whether looking at the long or short term, match theoretical predictions, and a significant slice of the empirical documentation corroborates these results (Razzaq, 2021;Caiyi et al, 2022;George et al, 2015). Moreover, the ECM (Error Correction Model) coefficient being significant and negative signifies an amending process in the long-term nexus between economic growth and solid waste recycling.…”
Section: Bootstrap Ardl Long-term and Short-term Estimatessupporting
confidence: 71%
“…The main finding of the study is that the nexus between environmental contaminants and income doesn't adhere to the Environmental Kuznets Curve (EKC) but rather takes on an N-shaped curve. Caiyi et al (2022) delve into the mien of the growth of the e-commerce industry on solid waste production in China. The analysis period of the investigation which opted for secondgeneration panel unit root and cointegration assessments has been determined as 2010-2015.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Liang,C.Y.,etal.(2022). [3] simulated and analyzed the connection between e-commerce industry and solid waste in eastern, central and western China through different mathematical models, with a view to providing a perspective and basis for China to formulate regional green laws and regulations to reduce solid waste discharge from e-commerce and open up a green development path for e-commerce. Explore the green development path of e-commerce from the perspective of solid waste.…”
Section: Current Situation Of Foreign Researchmentioning
confidence: 99%